Modeling of CO2 storage in aquifers - Savioli, Gabriela B. (2011)
Storage of CO2 in geological formations is a means of mitigating the greenhouse effect. Saline aquifers are a good alternative as storage sites due to their large volume and their common occurrence in nature. The first commercial CO2 injection project is that of the Sleipner field in the Utsira Sand aquifer (North Sea). Nevertheless, very little was known about the effectiveness of CO2 sequestration over very long periods of time. In this way, numerical modeling of CO2 injection and seismic monitoring is an important tool to understand the behavior of CO2 after injection and to make long term predictions in order to prevent CO2 leaks from the storage into the atmosphere. The description of CO2 injection into subsurface formations requires an accurate fluid-flow model. To simulate the simultaneous flow of brine and CO2 we apply the Black-Oil formulation for two phase flow in porous media, which uses the PVT data as a simplified thermodynamic model. Seismic monitoring is modeled using Biot's equations of motion describing wave propagation in fluid-saturated poroviscoelastic solids. Numerical examples of CO2 injection and time-lapse seismics using data of the Utsira formation show the capability of this methodology to monitor the migration and dispersal of CO2 after injection.